Characteristics of functional materials for gas storage applications - Ang, Melvin Shang Sheng (Nanyang Technological University, 2024)
As the world is desperately in need of sustainable solutions to handle the aftermath of utilizing non-sustainable fossil fuel power plants to meet the world’s energy demands, world researches are constantly finding sustainable methodologies to boost energy production of renewable power plants and reduce carbon levels in the world’s atmosphere. For the past decade, researchers have heavily devoted their time to exploring the promising potential of functional porous adsorbents such as metal-organic frameworks (MOFs) and activated carbons. Given the extensive research on MOFs, it does not cover the full range of conditions such as conducting adsorption experiments at cryogenic temperature. Therefore, this project aims to explore the adsorption capability of HKUST-1, Maxsorb-III and other functionalization of HKUST-1 in various cryogenic temperatures. This project primarily focuses on the characteristics and the adsorption performance of Maxsorb-III, HKUST-1, and its functionalities for hydrogen and carbon dioxide gas storage applications. The parent MOFs, namely HKUST-1, and the modified HKUST-1: Maxsorb-III (1:0.5), HKUST-1: Maxsorb-III (1:1) and HKUST-1: Maxsorb-III (1:2) are synthesized using the solvothermal method. The surfaces of these functional porous adsorbents are analyzed using scanning electron microscopy (SEM), thermogravimetric analysis (TGA) and adsorption experiment to characterize the adsorbent crystal surfaces, thermal stability and adsorption capability respectively. The TGA data reveals that the decomposition temperature of HKUST-1 and its functionalities is estimated to range from 275°C to 325°C while Maxsorb-III has a higher decomposition temperature of over 400°C. Gas adsorption experiments are carried out on an experimental setup capable of measuring hydrogen and carbon dioxide adsorption uptake at various cryogenic temperatures and pressures not exceeding 6 bars. The data extracted from the adsorption experiment are calculated and presented as isotherms to understand the adsorbent adsorption performance for a given temperature and pressure. All experimental and calculated data are provided in this report.